2013
DOI: 10.1159/000355387
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Leptin Predicts Adiposity of the Neonate

Abstract: Background: Increased adiposity at birth may identify infants at high risk of developing obesity. Maternal obesity and hyperglycemia in pregnancy are associated with increased neonatal adiposity; however, features of maternal obesity that contribute to increased neonatal adiposity need further study. Aims: To measure adiposity in neonates of obese and normal-weight women without gestational diabetes to test the hypothesis that obese women have neonates with increased adiposity compared to neonates of normal-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 35 publications
(47 reference statements)
4
49
2
8
Order By: Relevance
“…Another study suggested a reverse correlation between PI and adiponectin concentration (11,25). Some studies have shown a positive correlation between adiponectin concentration and birth weight (8,12,14,(16)(17)(18)(19)(20), but few have failed to find a significant correlation (9,15). The current study found a positive correlation between adiponectin concentration and gestational age in the GDM group although there was no such correlation in the NGT group.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Another study suggested a reverse correlation between PI and adiponectin concentration (11,25). Some studies have shown a positive correlation between adiponectin concentration and birth weight (8,12,14,(16)(17)(18)(19)(20), but few have failed to find a significant correlation (9,15). The current study found a positive correlation between adiponectin concentration and gestational age in the GDM group although there was no such correlation in the NGT group.…”
Section: Discussioncontrasting
confidence: 56%
“…Genes for lipid metabolism and those for inflammatory pathways are upregulated in the placenta of women with GDM (2). This upregulation increases or unbalances production of inflammatory cytokines and energy metabolism regulatory cytokines such as adipokines (2,6,7), which increases adiposity at birth (8,9) and predisposes the newborn to become overweight and develop metabolic diseases such as impaired glucose tolerance, metabolic syndrome, and cardiovascular disease (2,(6)(7)(8). Previous studies have focused on the pathophysiologic pathways and cytokine levels in GDM and their possible effect on offspring comorbidities later in life (1,6,7,10).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has two strong points that should be emphasized: the assessment of adiposity at birth by measuring the %FM using Maternal LCPUFA intake on offspring adiposity L Pereira-da-Silva et al ADP, as a reliable and precise method with recent increasing use; 16,17,26,27 and the assessment of the effect of maternal LCPUFA intake on the body composition at birth adjusted for three major maternal nutrition cofactors (prepregnancy BMI, energy and macronutrient intakes during pregnancy, and GWG).…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 studies have investigated the association between maternal leptin and neonatal adiposity [9,10]. They had opposing conclusions, leaving the question about leptin's role as a contributor to fetal adiposity wide open.…”
Section: Introductionmentioning
confidence: 99%